Evaluation of digested sludge as an amendment to chromium and lead contaminated Gangetic alluvial soils of India - BHAT, MOHAMMAD AUYOUB; AGARWAL, H P (The Indian Journal of Agricultural Sciences, 2013)
Indo-Gangetic belt of India possesses many industrial sites whereby effluents containing very high levels of heavy metals, especially Cr and Pb are directly discharged into the environment without any treatment or cleaning process leading to soil, plant and ecological toxicities. There has been increasing interest amongst scientific community to remediate the contaminated soils with cost-effective and environmentally safe methods. Keeping this in view, pot experiments were conducted to evaluate the effect of different levels of digested sludge addition to Gangetic alluvium, spiked with Cr or Pb up to 500 mg/kg on phytoxicity in corn (Zea mays L.) and radish (Raphanus sativus L.) plants. Increasing sludge levels resulted in decreased levels of DTPA-extractable Cr and Pb in the soil. The recovery of these metals by DTPA declined considerably with the duration following treatment application. Lowest biomass yield of test plants was observed in the treatment where no sludge was applied. Increasing levels of digested sludge enhanced the dry matter yields and decreased the tissue concentrations of Cr and Pb in plants. Plant tissue metal concentrations across all treatments decreased from first to second crop which could be ascribed to decrease in their DTPA-extractable levels in soil, a result of reversion of the metals into less available form with time. The findings reveal that digested sludge has a potential to reduce the phytoxicity of Cr and Pb and, therefore, can be used as an amendment for soils which have been adversely polluted with these metals by anthropogenic and industrial activities.